, Dwyer, Tessa. Speaking in subtitles. Revaluing screen translation. Edinburgh (UK): Edinburgh University Press, 2017, 240 p. - João Antonio Pimenta Ribeiro Neto (Cadernos de Tradução)
Tessa Dwyer’s Speaking in Subtitles. Revaluing Screen Translation deals mostly with the idea of "errancy” in audiovisual translation, specially subtitling. The book is divided in two parts, and each of these parts subdivided in three chapters. Before reading this book, it seemed like I was about to go on a trip of countless terminologies related to the Translation field, but the author manages to show some interesting facts about the evolution of what was first just a practice of translators into an academic area filled with subtleties. Dwyer also proposes an ample discussion about relevant themes to the area of Translation Studies such as the notions of fidelity and respect to the original text. And through that debate she comes to question the notion of what should be considered right or wrong in translation. She tries to deconstruct the so-called right way to translate an audiovisual product by introducing the idea of “errancy” and how inevitable it might be in some forms of audiovisual translation such as “fansubbing”, an underground and illegal way to make subtitles, and sometimes considered inferior to the official subtitles made by translators, yet a powerful tool to make audiovisual products accessible to the public who is not acquainted with a foreign language.